Śaivism and the Tantric Traditions Essays in Honour of Alexis G.J.S. Sanderson - Goodall, Dominic; Hatley, Shaman; Isaacson, Harunaga; Raman, Srilata (Gonda Indological Studies, 2020)
Academic study of the tantric traditions has blossomed in recent decades, in no small measure thanks to the magisterial contributions of Alexis G.J.S. Sanderson, until 2015 Spalding Professor of Eastern Religions and Ethics at Oxford University. This collection of essays honours him and touches several 􀀄􀀅elds of Indology that he has helped to shape (or, in the case of Śaivism, revolutionised): the history, ritual, and philosophies of tantric Buddhism, Śaivism and Vaiṣṇavism; religious art and architecture; and Sanskrit belles lettres. Former students and other experts in􀀆􀀇uenced by his scholarship here o􀀈fer papers that contribute signi􀀄􀀅cantly to our understanding of the cultural, religious, and intellectual histories of premodern South and Southeast Asia. Readership: Anyone interested in Asia's tantric traditions, philosophy and religion in premodern India, Sanskrit, and Indology. The book will be essential reading to specialists and advanced students of Śaivism and Tantric Buddhism.